Effects Of Design Factors And Shopping Types On Consumer Mood And Store Image In Korean Retail Market - Sang, Lin Han; Han, Dongchui (Asian Academy of Management (AAM), 2000)
In retailing, it is very important to examine how consumers perceive and react to instore design factors such as in-store space for walking, product arrangement styles, display types, and window sizes. This article investigates how various store designs create different consumer reactions depending on the types of consumer shopping in a Korean retail industry. It was found that design factors such as open, focused, and big created better consumer mood and consumer perception of store image than closed, unfocused, and small. Another finding is that consumer perceptions interact with consumer shopping patterns. Based on the research findings, managerial implications were also discussed